2014
DOI: 10.4149/bll_2014_0079
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of propofol and vitamin C administration on erythrocyte deformability in rats with streptozotocin-induced

Abstract: Abstract:Purpose: In the current study we aim to investigate the effects of vitamin C and profol on red blood cell deformability in diabetic rats Materials and methods: Twenty-eight Wistar Albino rats were included in the study after streptozocin (60 mg/ kg) treatment for 4 weeks of observation for diabetes presence. Twenty-eight rats were allocated to 4 groups. In group DP (n = 7) 150 mg.kg -1 of propofol was injected intraperitoneally. In group DP-vit C (n = 7) rats 100 mg/kg of vitamin C (Ascorbic acid, Red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Diyabetik ratlara 200mg/kg dozda E vitamini takviyesi yapıldığında plazma glukoz düzeyinin azalmadığı ancak MDA düzeyinin azaldığı ve antioksidan enzimlerle (CAT, GSH-PX, GSH-RD) antioksidan (E vitamini, C vitamini, ürik asit, eritrosit glutatyon düzeylerinin) normal seviyede olduğu tespit edilmiştir (53). Bir başka çalışmada diyabetik ratlara C vitamini verildiğinde eritrosit deformasyonunun düzeldiği görülmüştür (54). Melatoninle birlikte C ve E vitamini verilen diyabetik ratlarda plazma glukoz ve MDA düzeyleri azalmış, hematolojik ve biyokimyasal parametrelerle antioksidan düzeylerinin normale döndüğü görülmüştür (55).…”
Section: Deneysel çAlışmalarunclassified
“…Diyabetik ratlara 200mg/kg dozda E vitamini takviyesi yapıldığında plazma glukoz düzeyinin azalmadığı ancak MDA düzeyinin azaldığı ve antioksidan enzimlerle (CAT, GSH-PX, GSH-RD) antioksidan (E vitamini, C vitamini, ürik asit, eritrosit glutatyon düzeylerinin) normal seviyede olduğu tespit edilmiştir (53). Bir başka çalışmada diyabetik ratlara C vitamini verildiğinde eritrosit deformasyonunun düzeldiği görülmüştür (54). Melatoninle birlikte C ve E vitamini verilen diyabetik ratlarda plazma glukoz ve MDA düzeyleri azalmış, hematolojik ve biyokimyasal parametrelerle antioksidan düzeylerinin normale döndüğü görülmüştür (55).…”
Section: Deneysel çAlışmalarunclassified
“…In the past 20 or 30 years the prevalence of diabetes mellitus (DM) has rapidly increased throughout the world, and experts estimate that it is going to increase by 200 % in the next several decades (1).…”
Section: Introductionmentioning
confidence: 99%
“…Margolis et al showed that the rate of unrecognized myocardial infarction was 39 % in diabetic patients while in non-diabetic patients it was 22 % (3). Cardiac surgery with cardiopulmonary bypass inevitably causes a systemic infl ammatory response and ischemia-reperfusion (I/R) injury affecting multiple organs (1). Several drugs have been used to prevent I/R injury, including Vitamin C, levosimendan, and dexmedetomidine (1,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In last two or three decades, the prevalence of diabetes mellitus (DM) has rapidly increased throughout the world, and experts estimate that it will increase by 200 % in the next several decades (1). Erythrocyte deformability (ED) facilitates blood fl ow through the circulation in vessels of variable diameter and enables effective exchange of gas and metabolic products in capillaries (2).…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that the rate of unrecognised myocardial infarction was 39 % in diabetic patients and 22 % in non-diabetic patients (9). Cardiac surgery with cardiopulmonary bypass inevitably causes a systemic infl ammatory response and ischaemia-reperfusion (IR) injury affecting multiple organs (1).…”
Section: Introductionmentioning
confidence: 99%